Design of an experimental platform for hybridization of atomic and superconducting quantum systems - Landra, Alessandro (2019)
Hybrid quantum systems have the potential of mitigating current challenges in developing a scalable quantum computer. Of particular interest is the hybridization between atomic and superconducting qubits. We demonstrate an experimental setup for transferring and trapping ultracold atoms inside a millikelvin cryogenic environment, where interactions between atomic and superconducting qubits may be established, paving the way for hybrid quantum systems. We prepare 87Rb atoms in a conventional magneto-optical trap and transport them via a magnetic conveyor belt into a UHV compatible dilution refrigerator with optical access. We store 5×108 atoms with a lifetime of 794 s in the vicinity of the millikelvin stage.